2022
DOI: 10.1016/j.cmi.2022.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of factors promoting behaviour change toward antibiotic use in hospitals

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In a French study, the most common subcategories of enablement were audit and feedback [ 26 ]. In a recent study, the authors found that audit and feedback are a feasible and valuable methodology to assess the nationwide implementation of antibiotic stewardship programmes in hospitals [ 27 ]. Furthermore, it can identify relevant targets for the improvement of such programmes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a French study, the most common subcategories of enablement were audit and feedback [ 26 ]. In a recent study, the authors found that audit and feedback are a feasible and valuable methodology to assess the nationwide implementation of antibiotic stewardship programmes in hospitals [ 27 ]. Furthermore, it can identify relevant targets for the improvement of such programmes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here another aspect of AMS is in demand: the psychological point which extends beyond simple recommendations. A rationale use of antibiotics often implies a behavioural change [ 17 20 ].…”
Section: Discussionmentioning
confidence: 99%
“… 25 There is now agreement that only long-term and multifaceted interventions can lead to behaviour changes an improvement in prescribing. 26 These long-term engagements should be flanked by regular educational activities and point-prevalence studies to identify areas for improvement. 27 …”
Section: Discussionmentioning
confidence: 99%